Bernd Henningsen: Die Politik des Einzelnen. Ludvig Holberg, Søren Kierkegaard, N. F. S. Grundtvig. - Mortensen, Viggo (Grundtvig-Studier, 1977)
Bernd Henningsen: Die Politik des Einzelnen. Studien zur Genese der Skandinavischen Ziviltheologie. Ludvig Holberg. Søren Kierkegaard. N. F. S. Grundtvig. Studien zur Theologie und Geistesgeschichte des Neunzehnten Jahrhunderts Bd. 26. Vandenhoeck & Ruprecht, Göttingen 1977. Reviewed by Viggo Mortensen. The author of this doctorate, defended in Munich, sets out to track down the Danish, and thereby in his opinion, the Scandinavian national character. The problem for him as a politologist is why the great political upheavals, not to mention revolutions are absent from Scandinavian history. He looks for the spiritual background to this in the way the 19th century understood politics. That is, he wishes to analyse the relationship between the political events and the philosophical-historical tradition. What are the causes of this ‘immunity*, which in Scandinavia has prevented ideologies from becoming mass phenomena? Henningsen has found important contributions to an understanding of this problem in Holberg, Kierkegaard and Grundtvig. He characterises this political understanding with a concept from antiquity - ‘civil theology* - and with the English concept of ‘common sense’. The framework for his conception is constructed of various aspects of Danish social history and historical consciousness from the Danish Law (1683) to the ’Liberal Kulturkamp’ of the 1930’s, and Holberg is regarded as the father of Danish civil theology. Since it is the doctorate’s argument that continuity is a characteristic feature of Scandinavian civil theology, Kierkegaard is also included, his anti-clerical campaign being seen as a result of his awareness of his social-critical responsibility. But it is not really made clear what Kierkegaard’s contribution to Danish civil theology is, apart from his criticism of Hegel and his demand for an agreement between theory and practice. Grundtvig’s inclusion on the other hand is a matter of course. But he is given less room and treated more superficially than both Holberg and Kierkegaard. The writer quite rightly sees that Grundtvig is the clearest representative of the specifically Scandinavian attitude to the life of the spirit (’Geisteshaltung*). In particular, emphasis is placed on Grundtvig’s ideas of ’folkelighed’ (national spirit) and ’danskhed’ (Danishness). As Henningsen defines ’folkelighed’ as the sum total of a nation’s values, norms and behaviour, this concept becomes a definition of what is denoted by the key concept, civil theology - and thus becomes the key to our resistance to ideology. This point of view could and should have been developed and supported with more evidence. The main impression the book leaves is that Holberg is treated congenially, Kierkegaard with uncritical admiration, and Grundtvig with unacceptable brevity. However, the writer demonstrates wide reading and a close acquaintance with Danish cultural life. He believes that scholars who do not speak Danish must set about learning it, if they wish to be taken seriously as, for example, Kierkegaard scholars. This reviewer considers that the book reveals contexts and suggests lines of continuity that will provoke much thought.